2021
DOI: 10.1177/15353702211014185
|View full text |Cite
|
Sign up to set email alerts
|

Modeling adaptive drug resistance of colorectal cancer and therapeutic interventions with tumor spheroids

Abstract: Drug resistance is a major barrier against successful treatments of cancer patients. Various intrinsic mechanisms and adaptive responses of tumor cells to cancer drugs often lead to failure of treatments and tumor relapse. Understanding mechanisms of cancer drug resistance is critical to develop effective treatments with sustained anti-tumor effects. Three-dimensional cultures of cancer cells known as spheroids present a biologically relevant model of avascular tumors and have been increasingly incorporated in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 74 publications
0
5
0
Order By: Relevance
“…54,55 Over the past several years, we have developed tumor spheroid models of colorectal cancers for mechanistic studies of drug resistance and to test and identify effective treatment strategies. 56 Here, we leveraged our established 3D tumor spheroid model in a cyclic treatment regimen to demonstrate that colorectal cancer cells develop adaptive resistance to single-agent inhibition of MEK through feedback signaling and gain of stemness. We found that a combination treatment approach targeting MEK and CSCs effectively blocks adaptive resistance of cancer cells by suppressing tumor stemness.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…54,55 Over the past several years, we have developed tumor spheroid models of colorectal cancers for mechanistic studies of drug resistance and to test and identify effective treatment strategies. 56 Here, we leveraged our established 3D tumor spheroid model in a cyclic treatment regimen to demonstrate that colorectal cancer cells develop adaptive resistance to single-agent inhibition of MEK through feedback signaling and gain of stemness. We found that a combination treatment approach targeting MEK and CSCs effectively blocks adaptive resistance of cancer cells by suppressing tumor stemness.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Spheroid and organoid cultures of cancer cells have been leveraged to study mechanisms of drug resistance in different cancers. For example, a 3D model of colorectal cancer composed of cells derived from a primary tumor reproduced resistance to 5-FU treatment in the animal model, and an organoid culture model developed under an air-liquid interface contained CSCs and exhibited resistance to anticancer drugs. , Over the past several years, we have developed tumor spheroid models of colorectal cancers for mechanistic studies of drug resistance and to test and identify effective treatment strategies . Here, we leveraged our established 3D tumor spheroid model in a cyclic treatment regimen to demonstrate that colorectal cancer cells develop adaptive resistance to single-agent inhibition of MEK through feedback signaling and gain of stemness.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we demonstrate that EMMPRIN is an important participant in the formation of spheroids as a spatial organization of tumor cells, and that this organization and the expression of high levels of EMMPRIN promote cellular properties that enhance their ability to metastasize. Spheroids have emerged as a useful tool that more closely simulates the in vivo organization of solid tumors in comparison to the standard in vitro culturing approach of monolayers, and provide a better in vitro platform to study the enhanced metastatic properties of tumor cells ( 19 ). We emphasize that in our study the cells seeded as monolayers or spheroids were not stimulated in any other way, allowing us to assess the effects of the spatial organization alone.…”
Section: Discussionmentioning
confidence: 99%
“…The spherical structure creates gradients of oxygen and nutrients that generate heterogeneity in the rate of proliferation and metabolism of the spheroid cells, and in their expression of genes ( 16 , 17 ). Although these 3D structures are only an intermediate model of the tissue and do not fully model the intricate interactions between cells and their neighboring cells or the tissue-specific extracellular matrix (ECM) components ( 18 ), spheroids have become a relevant in vitro model to study the development of resistance to chemotherapeutic treatment ( 19 ) and a high throughput screening platform for drugs ( 20 ). However, other than E-cadherin and integrins, the proteins mediating the cell-cell interactions that form the spheroid structure are still not well characterized ( 21 ).…”
Section: Introductionmentioning
confidence: 99%
“…Our previous studies used spheroid cultures of cancer cell lines in cyclic treatments to establish the feasibility of investigating mechanisms of drug resistance and testing the efficacy of different drug combinations [ 16 ]. Using primary cancer cells is critical to facilitate translational potential of this approach.…”
Section: Introductionmentioning
confidence: 99%